-2x^2-4+6x=0
Tim x,
a,2x^4-6x^3+x^2+6x-3=0
b,x^3-9x^2+26x+24=0
c, P= 2x^4 - 4x^3 + 6x^2 - 4x + 5 biet rang x^2 - x=7
a)\(2x^4-6x^3+x^2+6x-3=0\)
\(\Leftrightarrow2x^4-6x^3+3x^2-2x^2+6x-3=0\)
\(\Leftrightarrow x^2\left(2x^2-6x+3\right)-\left(2x^2-6x+3\right)=0\)
\(\Leftrightarrow\left(x^2-1\right)\left(2x^2-6x+3\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(x+1\right)\left(2x^2-6x+3\right)=0\)
\(\Leftrightarrow\left[\begin{array}{nghiempt}x-1=0\\x+1=0\\2x^2-6x+3=0\end{array}\right.\)\(\Leftrightarrow\left[\begin{array}{nghiempt}x=1\\x=-1\\\Delta_{2x^2-6x+3}=\left(-6\right)^2-4\left(2.3\right)=12\end{array}\right.\)
\(\Leftrightarrow\left[\begin{array}{nghiempt}x=1\\x=-1\\x_{1,2}=\frac{6\pm\sqrt{12}}{4}\end{array}\right.\)
b)\(x^3+9x^2+26x+24=0\)
\(\Leftrightarrow x^3+5x^2+6x+4x^2+20x+24=0\)
\(\Leftrightarrow x\left(x^2+5x+6\right)+4\left(x^2+5x+6\right)=0\)
\(\Leftrightarrow\left(x^2+5x+6\right)\left(x+4\right)=0\)
\(\Leftrightarrow\left(x+2\right)\left(x+3\right)\left(x+4\right)=0\)
\(\Leftrightarrow\left[\begin{array}{nghiempt}x+2=0\\x+3=0\\x+4=0\end{array}\right.\)\(\Leftrightarrow\left[\begin{array}{nghiempt}x=-2\\x=-3\\x=-4\end{array}\right.\)
Giải bất phương trình sau : a/ 2x ^ 2 + 6x - 8 < 0 x ^ 2 + 5x + 4 >=\ 2) Giải phương trình sau : a/ sqrt(2x ^ 2 - 4x - 2) = sqrt(x ^ 2 - x - 2) c/ sqrt(2x ^ 2 - 4x + 2) = sqrt(x ^ 2 - x - 3) b/ x ^ 2 + 5x + 4 < 0 d/ 2x ^ 2 + 6x - 8 > 0 b/ sqrt(- x ^ 2 - 5x + 2) = sqrt(x ^ 2 - 2x - 3) d/ sqrt(- x ^ 2 + 6x - 4) = sqrt(x ^ 2 - 2x - 7)
2:
a: =>2x^2-4x-2=x^2-x-2
=>x^2-3x=0
=>x=0(loại) hoặc x=3
b: =>(x+1)(x+4)<0
=>-4<x<-1
d: =>x^2-2x-7=-x^2+6x-4
=>2x^2-8x-3=0
=>\(x=\dfrac{4\pm\sqrt{22}}{2}\)
a, 6x^3-6x=0
b, 2x(3x+7) -6x^2=28
c, 2(4x+4)-5(x-3)=0
a) \(6x^3-6x=0\Leftrightarrow6x\left(x^2-1\right)=0\Leftrightarrow6x\left(x-1\right)\left(x+1\right)=0\Leftrightarrow\left[{}\begin{matrix}6x=0\\x-1=0\\x+1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=0\\x=1\\x=-1\end{matrix}\right.\)b) \(2x\left(3x+7\right)-6x^2=28\Leftrightarrow6x^2+14x-6x^2=28\Leftrightarrow14x=28\Leftrightarrow x=2\)
c) \(2\left(4x+4\right)-5\left(x-3\right)=0\Leftrightarrow8x+8-5x+15=0\Leftrightarrow3x=-23\Leftrightarrow x=-\dfrac{23}{3}\)
a: Ta có: \(6x^3-6x=0\)
\(\Leftrightarrow6x\left(x-1\right)\left(x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=-1\\x=1\end{matrix}\right.\)
b: Ta có: \(2x\left(3x+7\right)-6x^2=28\)
\(\Leftrightarrow6x^2+14x-6x^2=28\)
\(\Leftrightarrow14x=28\)
hay x=2
c: Ta có: \(2\left(4x+4\right)-5\left(x-3\right)=0\)
\(\Leftrightarrow8x+8-5x+15=0\)
\(\Leftrightarrow3x=-23\)
hay \(x=-\dfrac{23}{3}\)
x2-4x+4=9
(x-7)(2x+5)=0
4x2-6x=0
4(3x-2)-3(x-4)=7x+10
2x(x+3)+5 (x+3)=0
2x (x-3)-5 ( x-3)=0
x3-6x2+5x=0
Giúp mình
4x^4+6x^3+2x^2+6x-4=0
a) (2x +1)(3 – x)(4 - 2x) = 0 b)2x(x – 3) + 5(x – 3) = 0
c) (x2 – 4) – (x – 2)(3 – 2x) = 0 d) x2 – 5x + 6 = 0
e) (2x + 5)2 = (x + 2)2 f) 2x3 + 6x2 = x2 + 3x
a: (2x+1)(3-x)(4-2x)=0
=>(2x+1)(x-3)(x-2)=0
hay \(x\in\left\{-\dfrac{1}{2};3;2\right\}\)
b: 2x(x-3)+5(x-3)=0
=>(x-3)(2x+5)=0
=>x=3 hoặc x=-5/2
c: =>(x-2)(x+2)+(x-2)(2x-3)=0
=>(x-2)(x+2+2x-3)=0
=>(x-2)(3x-1)=0
=>x=2 hoặc x=1/3
d: =>(x-2)(x-3)=0
=>x=2 hoặc x=3
e: =>(2x+5+x+2)(2x+5-x-2)=0
=>(3x+7)(x+3)=0
=>x=-7/3 hoặc x=-3
f: \(\Leftrightarrow2x^3+5x^2-3x=0\)
\(\Leftrightarrow x\left(2x^2+5x-3\right)=0\)
\(\Leftrightarrow x\left(x+3\right)\left(2x-1\right)=0\)
hay \(x\in\left\{0;-3;\dfrac{1}{2}\right\}\)
Tìm x:
a) x2+6x+5=0
b) 2x2+6x+4=0
a)\(x^2+6x+5=0\)
=>\(x^2+x+5x+5=0\)
=>\(x\left(x+1\right)+5\left(x+1\right)=0\)
=>\(\left(x+1\right)\left(x+5\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x+1=0\\x+5=0\end{cases}\Rightarrow\orbr{\begin{cases}x=-1\\x=-5\end{cases}}}\)
Vậy x=-1 hoặc x=-5
b)\(2x^2+6x+4=0\)
=>\(2x^2+2x+4x+4=0\)
=>\(2x\left(x+1\right)+4\left(x+1\right)=0\)
=>\(\left(x+1\right)\left(2x+4\right)=0\)
=>\(\left(x+1\right)2\left(x+2\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x+1=0\\x+2=0\end{cases}\Rightarrow\orbr{\begin{cases}x=-1\\x=-2\end{cases}}}\)
Vậy x=-1 hoặc x=-2
a) \(x^2+6x+5=0\)
\(x.\left(x+6\right)=-5=-1.5=-5.1=1.-5=5.-1\)
Có 4 th
\(x.\left(x+6\right)=-1.5\)\(\Rightarrow\hept{\begin{cases}x=-1\\x+6=5\end{cases}}\Rightarrow\hept{\begin{cases}x=-1\\x=-1\end{cases}}\)
\(x.\left(x+6\right)=5.-1\Rightarrow\hept{\begin{cases}x=5\\x+6=-1\end{cases}}\Rightarrow\hept{\begin{cases}x=5\\x=-7\end{cases}}\)
\(x.\left(x+6\right)=1.-5\Rightarrow\hept{\begin{cases}x=1\\x+6=-5\end{cases}}\Rightarrow\hept{\begin{cases}x=1\\x=-11\end{cases}}\)
\(x.\left(x+6\right)=-5.1\Rightarrow\hept{\begin{cases}x=-5\\x+6=1\end{cases}}\Rightarrow\hept{\begin{cases}x=-5\\x=-5\end{cases}}\)
=> x = {-1;-5}
a) -x^4+2x^3-2x^2+2x-3=0
b) x^3-6x^2+11x-12=0
b) \(x^3-6x^2+11x-12=0\)
\(\Leftrightarrow\)\(x^3-4x^2-2x^2+8x+3x-12=0\)
\(\Leftrightarrow\)\(x^2\left(x-4\right)-2x\left(x-4\right)+3\left(x-4\right)\)
\(\Leftrightarrow\)\(\left(x-4\right)\left(x^2-2x+3\right)=0\)
Ta có: \(x^2-2x+3\)
\(=\left(x-1\right)^2+2>0\)
\(\Rightarrow\)\(x-4=0\)
\(\Leftrightarrow\)\(x=4\)
Vậy...
7)(16-8x)(2-6x)=0
8) (x+4)(6x-12)=0
9) (11-33x)(x+11)=0
10) (x-1/4)(x+5/6)=0
11) (7/8-2x)(3x+1/3)=0
12)3x-2x^2=0
7)(16-8x)(2-6x)=0
=> 16 - 8x = 0 hoặc 2 - 6x = 0
=> 16 = 8x hoặc 2 = 6x
=> x = 2 hoặc x = 1/3
8) (x+4)(6x-12)=0
=> x + 4 = 0 hoặc 6x - 12 = 0
=> x = -4 hoặc x = 2
9) (11-33x)(x+11)=0
=> 11 - 33x = 0 hoặc x + 11 = 0
=> x = 1/3 hoặc x = -11
10) (x-1/4)(x+5/6)=0
=> x - 1/4 = 0 hoặc x + 5/6 = 0
=> x = 1/4 hoặc x = -5/6
11) (7/8-2x)(3x+1/3)=0
=> 7/8 - 2x = 0 hoặc 3x + 1/3 = 0
=> 2x = 7/8 hoặc 3x = -1/3
=> x = 7/16 hoặc x = -1/9
12)3x-2x^2=0
=> x(3 - 2x) = 0
=> x = 0 hoặc 3 - 2x = 0
=> x = 0 hoặc x = 3/2
\(a,\left(16-8x\right)\left(2-6x\right)=0\)
\(\hept{\begin{cases}16-8x=0\\2-6x=0\end{cases}\Rightarrow\hept{\begin{cases}x=2\\x=\frac{1}{3}\end{cases}}}\)
\(b,\left(x+4\right)\left(6x-12\right)=0\)
\(\hept{\begin{cases}x+4=0\\6x-12=0\end{cases}\Rightarrow\hept{\begin{cases}x=-4\\x=2\end{cases}}}\)
\(c,\left(11-33x\right)\left(x+11\right)=0\)
\(\hept{\begin{cases}11-33x=0\\x+11=0\end{cases}\Rightarrow\hept{\begin{cases}x=\frac{1}{3}\\x=-11\end{cases}}}\)
\(d,\left(x-\frac{1}{4}\right)\left(x+\frac{5}{6}\right)=0\)
\(\hept{\begin{cases}x-\frac{1}{4}=0\\x+\frac{5}{6}=0\end{cases}\Rightarrow\hept{\begin{cases}x=\frac{1}{4}\\x=-\frac{5}{6}\end{cases}}}\)
\(e,\left(\frac{7}{8}-2x\right)\left(3x+\frac{1}{3}\right)=0\)
\(\hept{\begin{cases}\frac{7}{x}-2x=0\\3x+\frac{1}{3}=0\end{cases}\Rightarrow\hept{\begin{cases}x=\frac{7}{4}\\x=-\frac{1}{9}\end{cases}}}\)
\(f,3x-2x^2=0\)
\(x\left(3-2x\right)=0\)
\(\hept{\begin{cases}x=0\\3-2x=0\end{cases}\Rightarrow\hept{\begin{cases}x=0\\x=\frac{3}{2}\end{cases}}}\)